Seasonal Cointegration in Macroeconomic Systems: Case Studies for Small and Large European Countries - Kunst, Robert M. (The Review of Economics and Statistics, 1993)
Six-variable vector autoregressive systems consisting of macroeconomic series are investigated. parallel data series for four european countries are used: austria, germany (federal republic), finland, and the united kingdom. all data series are not seasonally adjusted. the aim of the paper is to show that most of the series are better modeled using stochastic seasonality and seasonal unit roots models than simple deterministic models of seasonal structures. as a second step, seasonal cointegration in the systems is studied. it is shown that all four economies display seasonal cointegration as well as usual cointegration.;